Interação da rizipiscicultura com agroquímicos e efeitos sobre a comunidade zooplanctônica - Golombieski, Jaqueline Ineu (2006)
The objective of this experiment was to determine the lethal concentration (LC50;96h) of azimsulfuron (A) and metsulfuron-methyl (M) herbicides and carbofuran (C) insecticide for common (Cyprinus carpio), grass (Ctenopharyngodon idella )and big head (Aristichthys nobilis) carps fingerlings, and the effect of these pesticides on the cholinergics response in fish; to quantify the survival and growth of common, grass and bighead carps fingerlings in rice fields, that were subjected to pesticides; to estimate the effect of the pesticides in the zooplankton community present in the water of irrigation rice and quantify the rice farming production in rice-fish culture. The experiments were divided in experiment 1 (LC50;96h determination for fish), fulfilled in laboratory and experiment 2 (exposure of carps and zooplankton in rice fields), carried in lowland area of Departament of Fitotecnia (UFSM). In experiment 1 the carps (10 fingerlings/replicate) were exposed to the pesticides for 96 h in a entirely randomized experiment (three replicates), evaluating the survival and swimming behaviors of the fishes. Surviving fishes were frozen and brain and muscle removed for acetilcholinesterase enzyme analysis (AChE). The experiment 2, carried in growing seasons 2003/04 and 2004/05 in a randomized complete block experiment with four replicates (experimental units 48 m2- 8mx6m), started with rice seeding in pre-germinate system, and pesticides application with eight treatments: T1- A+fish; T2- M+ fish; T3- C+ fish; T4- A+M+C+ fish; T5- A+M+C (without fish); T6- A+M+ fish; T7- control 1 (only rice); T8- control 2 (rice+ fish). After eight days of the pesticides application, fish were placed in refuge area, where remained during the whole rice culture until October. In this period, the zooplankton collection was fulfilled 17 days before pesticides application up to 75th days after this application. Results allon to 14 conclude that LC50;96h carbofuran was 1.81 mg/L for common carp, 2.71 mg/L for grass carp and 2.37 mg/L for bighead carp. This study showed that doses of carbofuran near that applied in rice culture (0.75 mg/L) provoked mortality and affected behavior and AChE activity in the studied species (Cyprinus carpio, Ctenopharyngodon idella, and Aristichthys nobilis), indicating that the use of this insecticide is not recommended for rice-fish culture system. For experiment 2, the application of pesticides (carbofuran, azimsulfuron and metsulfuron-methyl) in rice farming did not affect survival of common, grass and bighead carps when fingerlings are put eight days after pesticides application. At this moment, waterborne carbofuran concentrations were 0.025 and 0.144 mg/L (years 1 and 2 respectively), and these levels can be considered of low toxicity for fish. Rice productivity was not influenced by these pesticides when the continuous flooding management was used after pre-germinated rice sow. The rice productivity in year 1 was 4151 kg ha-1, and in year 2, 5643 kg ha-1. Carbofuran application provoked negative effects in zooplankton community of the rice-fish culture, for Cladocers group. Copepods (adults and nauplius), and Rotifers were slighly affected by carbofuran application. Adults Copepods were affected by the presence of fish in the treatments.